Cultural predictors of decision effectiveness: Experimental study with Argentine peacekeepers - Depaula, Pablo Domingo (2018)
The study proposes to explore a model of cultural variables predictive of the effectiveness of decision making in environments whose culture differs from that of decision makers. An intentional non-probabilistic sample was composed of 130 peacekeepers. Participants responded to an experimental decision-making task in situations of high or low saturation of cultural elements typical of the Republic of Haiti (where they would participate in a peace mission under the UN mandate during the subsequent semester), and completed the Cultural Intelligence Scale (CQS; Ang et al., 2007; Depaula adaptation, 2010). A linear stepwise regression analysis indicated that 19.4% of the variance in the effectiveness of decisions made by peacekeepers depends on the cultural behaviors (verbal and non-verbal) that they display and the level of cultural saturation of situations.